Helminths and intestinal barrier function. Issue 1 (2nd January 2017) - McKay, Derek M.; Shute, Adam; Lopes, Fernando
ABSTRACT: Approximately one-sixth of the worlds' population is infected with helminths and this class of parasite takes a major toll on domestic livestock. The majority of species of parasitic helminth that infect mammals live in the gut (the only niche for tapeworms) where they contact the hosts' epithelial cells. Here, the helminth-intestinal epithelial interface is reviewed in terms of the impact on, and regulation of epithelial barrier function, both intrinsic (epithelial permeability) and extrinsic (mucin, bacterial peptides, commensal bacteria) elements of the barrier. The data available on direct effects of helminths on epithelial permeability are scant, fragmentary and pales in comparison with knowledge of mobilization of immune reactions and effector cells in response to helminth parasites and how these impact intestinal barrier function. The interaction of helminth-host and helminth-host-bacteria is an important determinant of gut form and function and precisely defining these interactions will radically alter our understanding of normal gut physiology and pathophysiological reactions, revealing new approaches to infection with parasitic helminths, bacterial pathogens and idiopathic auto-inflammatory disease.